Increased procedural safety of cryoballoon pulmonary vein isolation with a double 120 s freeze protocol. Issue 8 (29th June 2021) - Bianchini, Lorenzo; Bordignon, Stefano; Chen, Shaojie; Zanchi, Simone; Tohoku, Shota; Bologna, Fabrizio; Tondo, Claudio; Schmidt, Boris; Chun, K.R. Julian
Abstract: Background: Recently a double 120 s freeze cryoballoon (CB) pulmonary vein isolation (PVI) protocol proved to be non inferior to a double 240 s freeze protocol in terms of atrial fibrillation (AF) recurrences. We hypothesized that this approach could also result in an increased procedure safety. Methods: Eighty consecutive patients treated with a double 120 s freeze protocol (Group CB120) were compared with 80 previous consecutive patients treated with a single 240 s freeze protocol (Group CB240). Procedures were performed with a temperature probe to monitor the luminal esophageal temperature (LET), using a cut off for cryoenergy interruption of 15°C. During ablation at the septal pulmonary veins (PVs), the phrenic nerve (PN) function was monitored by pacing. Results: In CB120 and CB240 the rate of single shot isolation was similar in all PVs. Time to isolation was not different between the two groups. Mean minimal esophageal temperature was lower in LSPV and LIPV of the CB240 group. A total of 4/80 patients (5%) of the CB120 group experienced a PN injury, but no persistent form was recorded; 11/80 patients (14%) of the CB240 group experienced a PN injury, three in a persistent form ( p  = .10). A LET <15°C was recorded in 3/80 patients (4%) in the CB120 group and in 16/80 patients (20%) in the CB240 group ( p  < .01). Composite rate of energy‐related safety events (LET <15°C and PN injury) was significantly lower in the CB120 (34% vs. 9%, p  < .01). Conclusions: Safety of second generation CB PVI can be increased using a double 120 s freeze protocol.